Genetic Analysis of a Unique Bacteriocin, Smb, Produced by Streptococcus mutans GS5 - Yonezawa, Hideo (American Society for Microbiology, 2005)
A dipeptide lantibiotic, named Smb, in Streptococcus mutans GS5 was characterized by molecular genetic approaches. The Smb biosynthesis gene locus is encoded by a 9.5-kb region of chromosomal DNA and consists of seven genes in the order smbM1, -T, -F, -M2, -G, -A, -B. This operon is not present in some other strains of S. mutans, including strain UA159. The genes encoding Smb were identified as smbA and smbB. Inactivation of smbM1, smbA, or smbB attenuated the inhibition of the growth of the indicator strain RP66, confirming an essential role for these genes in Smb expression. Mature Smb likely consists of the 30-amino-acid SmbA together with the 32-amino-acid SmbB. SmbA exhibited similarity with the mature lantibiotic lacticinA2 from Lactococcus lactis, while SmbB was similar to the mersacidin-like peptides from Bacillus halodurans and L. lactis. We also demonstrated that Smb expression is induced by the competence-stimulating peptide (CSP) and that a com box-like sequence is located in the smb promoter region. These results suggest that Smb belongs to the class I bacteriocin family, and its expression is dependent on CSP-induced quorum sensing.